O desenvolvimento profissional do professor formador iniciante no Ensino Superior: uma análise das dissertações e teses (2008 a 2018) - Gonçalves, Marta de Oliveira (2019)
The present thesis deals with the professional development of the beginning teacher in higher education that works in undergraduate courses, therefore, teacher trainer of the basic school. The general objective was to investigate the tendencies of academic productions that address the professional development of these beginner teachers in the period between 2008 and 2018. The methodology adopted in this thesis was the systematic review (ROMANOWSKI, 2002; FIORENTINI, PASSOS; LIMA, 2016; VOSGERAU; ROMANOWSKI , 2014). Searches were conducted at the Brazilian Digital Library of Theses and Dissertations (BDTD), which resulted in twelve studies, six dissertations and six theses that focused on the professional development of the beginning teacher education. With the in-depth reading of the studies, we sought to analyze trends, facilitators aspects and difficulties of professional development. Theoretical basis was studies on professional teacher development focusing on the beginning of teaching and the specificities of the work of the teacher education. Authors such as Day (2001); Marcelo (1999, 2006, 2009); Altet, Paquay and Perrenoud (2003); Vaillant (2003); Vaillant and Marcelo (2012); Gatti (2018); Ruiz (2008); Cunha (2014) and Steps (2018) were essential for the analysis. The tendency of most studies is to point out the difficult aspects such as the lack of pedagogical training and the solitude of the beginning trainer due to lack of systematized institutional support. On the other hand, they point out as facilitators the dialogue and the exchange between peers and reiterate the importance of the host programs. It is considered that systematized institutional support is needed so that the beginning teacher has more confidence in his practices and thus improves his work as a teacher education